NOVEL RUNX1 VARIATION IN B-CELL ACUTE LYMPHOBLASTIC LEUKEMIA - Qipa, Egzona; Acar, Muradiye; Bozkurt, Sureyya; Buyukdogan, Murat; Sonmez, Hazal Berivan; Sayitoglu, Muge; Erbilgin, Yucel; Karakas, Zeynep; Hancer, Veysel Sabri (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Acute lymphoblastic leukemia (ALL) is a malignant disease of hematopoietic stem cells. B cell ALL (B-ALL) is characterized by highly proliferative and poorly differentiated progenitor B cells in the bone marrow. Chromosomal rearrangements, aberrant cell signaling, and mutations lead to dysregulated cell cycle and clonal proliferation of abnormal B cell progenitors. In this study, we aimed to examine hot spot genetic variations in the RUNX1, IDH2, and IL2RA genes in a group of (n=52) pediatric B-ALL. Sanger sequencing results revealed a rare RUNX1 variant p.Leu148Gln in one B-ALL patient with disease recurrence. Additionally, common intronic variations rs12358961 and rs11256369 of IL2RA were determined in two patients. None of the patients had the IDH2 variant. RUNX1, IDH2, and IL2RA variations were rare events in ALL. This study detected a novel pathogenic RUNX1 variation in a patient with a poor prognosis. Examining prognostically important genetic anomalies of childhood lymphoblastic leukemia patients and the signaling pathway components will pilot more accurate prognosis estimations.